Dividend policy, ownership structure and corporate governance: An empirical analysis of Indonesian firms - Ronny Malavia Mardani (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2022)
The purpose of this study is to determine whether there is a correlation between dividend policy, ownership structure, and corporate governance. Dividend policy is quantified through the Dividend Payout Ratio, the ownership structure is quantified through the management and institutional ownership, and corporate governance is quantified through the presence of a board of directors and an independent board. There are 55 companies from 97 as part of the research, financial firms that are publicly traded on the Indonesian stock exchange were gathered as a sample. Data analysis techniques were performed using ordinary least square regression. Furthermore, based on the findings of the study, it can be concluded that managerial ownership has a positive relationship to dividend policies. The dividend policy of a company is negatively correlated with institutional ownership. The size of the board has a negative relationship with dividend policy; however, an independent board has a positive relationship with dividend policy. Profitability is positively correlated with dividend payments. The characteristics of financial firms that differ from the main industrial sector companies in terms of capital structure, so that it provides the same contribution as other industrial sectors to dividend payments, the capital structure is inversely proportional to dividend payments.